PARTNERSHIP OF GARLIC FARMERS AND IMPORTERS IN KARANGANYAR REGENCY - Ricky Ricky; Suminah Suminah; Eksa Rusdiyana (International Journal of Social Science, 2022)
Garlic planting program is the implementation of Republic of Indonesia Minister of Agriculture’s Regulation Number 16 of 2017 about Horticultural Product Import Recommendation (RIPH). This garlic planting program was conducted by importer along with partner farmer group in Sepanjang and Nglebak Villages, Karanganyar Regency in 2018. The objectives of research are to describe the implementation of Republic of Indonesia Minister of Agriculture’s Regulation Number 16 of 2017 in the program conducted by importer in Karanganyar Regency and to study the implementation of garlic planting partnership program conducted by importer based on CIPP evaluation. The research method used was descriptive qualitative one. The result of research shows that the implementation of Republic of Indonesia Minister of Agriculture’s Regulation Number 16 of 2017 by importer along with farmer group in Sepanjang and Nglebak Villages was conducted with 128 participants and 18.1 Ha land width. Evaluation on the garlic planting partnership program between importer and farmers in Sepanjang and Nglebak Villages using CIPP does not achieve result as targeted. The implementation of garlic planting is not as planned. Poor quality of garlic seeds and planting period incompatible to the condition of Tawangmangu Sub District area made this program failed and unsustainable.